Role Of Eco-Literacy in Developing Sustainable Behaviors Among Higher Secondary Students of District Faisalabad - Sidra Sadaf; Dr. Rana M. Amir; Syed Karam Murtaza; Tehseen Zahra; Dr. Rao Sabir Sattar; Nida Khursheed; Hafiz Muhammad Abdullah; Sonia (Social Science Review Archives, 2025)
Eco-literacy is the understanding of ecological systems and the ability to make informed, responsible environmental decisions. This study explored the role of eco-literacy in promoting sustainable behavior among higher secondary students in public sector colleges of Faisalabad a city facing serious environmental challenges like water scarcity, smog, extreme weather, and poor waste management. From the 51 public colleges listed by the Directorate of Education Faisalabad, four were selected using convenience sampling. Out of a population of 2,800 students, a sample of 244 was chosen using a 95% confidence level and 6% confidence interval, with equal gender and rural–urban representation. A descriptive research design was employed, using a structured questionnaire. Data were analyzed using SPSS. The findings revealed a strong positive relationship between eco-literacy and environmentally responsible behavior. Female students exhibited greater ecological responsibility compared to male students (p = .000). Most respondents demonstrated high eco-literacy levels, influenced by curriculum content, previous knowledge, and college-based initiatives like recycling drives. Students showed significant interest in environmental issues, particularly in waste management, and many supported awareness campaigns and practical initiatives. However, opinions were divided regarding enforcement measures such as fines and government regulation. The study concludes that enhancing eco-literacy can significantly contribute to environmental sustainability. It recommends making environmental education a compulsory part of the curriculum in public colleges, initiating more hands-on conservation programs, and enforcing environmental laws more strictly to cultivate a responsible and eco-conscious generation in Faisalabad.